Antibiotics alone for uncomplicated acute appendicitis in high operative risk adult patients: Analytical review of RCTs and proposal of evidence based treatment decision - Abongwa, Hariscine Keng; Cervellin, G; Tarasconi, A; Perrone, G; Baiocchi, G.; Portolani, N; Catena, F. (Acta Biomedica Atenei Parmensis, 2017)
Background: Clinical trials have so far shown controversial results as regards the standard of care for treating uncomplicated acute appendicitis (uC-AA). High operational risk adult patients (HORAP) could represent selected patients where primary antibiotic conservative therapy (pACT or A) could be indicated. Methods: We carried a comprehensive search of the PubMed searching engine in the English language scientific literature from 1995 to 2015, using medical subject headings “antibiotics”, “uncomplicated appendicitis”, “appendicectomy”, “conservative treatment”, “surgery” and “randomized clinical trial”. All RCTs comparing the outcomes of pACT versus primary surgical open or laparoscopic appendectomy (pSOLA or S) as primary treatment options for uC-AA were identified. Inclusion criteria for our analytical review were RCTs evaluating outcomes in terms of or related to all of the following four parameters: treatment efficacy, post therapeutic/operative complications, in hospital length of stay (LOS) and recurrence. Results: The conclusion of all five RCTs considered antibiotics alone in the treatment of AA as an efficient and non inferior therapeutic option respect to surgery. Primary ACT was characterised by a higher LOS, a higher rate of recurrence and a lower rate of postoperative complication than pSOLA. Conclusions: Based on the current body of evidence, an appropriate pACT could be a rational tailored primary treatment option for CT proven uC-AA in HORAP. Accurate diagnoses and surgical risk stratification in patients with uC-AA could aid decision making for target therapy. However, results of large sample prospective multicenter RCTs are required to routinely recommend pACT for uC-AA in the clinical practice.